Regulation of Metabolic Disease-Associated Inflammation by Nutrient Sensors - Alex S. Yamashita; Thiago Belchior; Fábio S. Lira; Nicolette C. Bishop; Barbara Wessner; José C. Rosa; William T. Festuccia (Mediators of Inflammation)
Visceral obesity is frequently associated with the development of type 2 diabetes (T2D), a highly prevalent chronic disease that features insulin resistance and pancreatic β-cell dysfunction as important hallmarks. Recent evidence indicates that the chronic, low-grade inflammation commonly associated with visceral obesity plays a major role connecting the excessive visceral fat deposition with the development of insulin resistance and pancreatic β-cell dysfunction. Herein, we review the mechanisms by which nutrients modulate obesity-associated inflammation.